USE OF THE FUZZY MODEL ON TRAFFIC BEHAVIOR IN DETERMINATION TIME OF INTERSECTION SIGNAL - Duddy Studyana, Moch
A fuzzy model is developed to address traffic behavior in determination signal time at intersection. The traffic is regulated using traffic signal. Restricted to a fixed time and isolated signal system, our simulation and case studies show that the proposed method offers benefit in term of better performance, over the conventional method. The proposed fuzzy model involves fuzzification of data, fuzzy inference engine, and defuzzification of the output of the inference engine. One of the main benefit of fuzzy model, is that our model is able to involve linguistic parameters, as well as quantitative ones; it is one distinctive character of fuzzy model that the system may involve uncertainties, ambiguities coming from human language. The proposed model is tested against real data coming from data acquisition from several samples of intersections in Bandung, during the period of May-June 2017. Analysis of the proposed method shows an average of 55% extension of green time over existing condition. Improvement of intersection performance is indicated by decrease of the length of vehicle queues, and the increase of intersection capacity; therefore the proposed method offers contribution to a better regulation of traffic signals at isolated intersections. Similar approach can be further developed for other types of traffic signals.